Older people’s knowledge about and access to the geriatrics service of Mogi das Cruzes, São Paulo - de Souza, Angela Alves Correia (2016)
Objective: To assess older people’s knowledge about and access to the geriatrics service of a polyclinic located in Mogi das Cruzes, São Paulo. Methods: Participants were 200 older people waiting for an outpatient consultation in the waiting room of the Polyclinic of the University of Mogi das Cruzes. These older people answered a questionnaire in the period from September 2013 to January 2014. Results: 58% (n=116) of participants reported knowing about the existence of a geriatric physician, but only 9,5% (n=19) were served by this specialist. Regarding older people who are usually served by one single medical specialty in routine consultations, 8% (n=16) sought specialists other than general practitioner, cardiologist and gynecologist. As for these other specialties, only 17.6% (n=35) sought the geriatrician. Most participants (99.5%, n=199) think it is important that older people are seen by a geriatric physician. Conclusion: Most older interviewees know the geriatric specialty; however, they never had the opportunity to consult a geriatric physician even though they recognize that this should occur. Despite the existence of this specialty in the polyclinic, it can be said that the population is not informed about the availability of consultations with such professional in the municipal service.